Summer with my cowboy - Miller, Linda Lael; Yates, Maisey (Kensington Publishing Corporation, 2026)
A painful divorce has brought Kendra Spencer home from Seattle to sunny Copper Ridge, Arizona. Despite a comfortable settlement, Kendra needs to keep busy-and keep herself from stalking her ex on social media. So she starts waitressing at the local diner, finding comfort in the regulars and her thankfully ordinary days. . . . Until far from ordinary newcomer Gage Elder walks in. Not only is he a champion bronc rider, turns out he's a widower-and maybe the one man understanding enough, kind enough-not to mention charming enough-to inspire Kendra to put the past behind her, and open her heart once more ... --